Ideologiâ i vnyšenie v ezoteričeskoj literaturę (na materiale Mulbaevaševa o Gorobe Bogov) - Dement’ev, Vadim V. (Stylistyka, 2019)
The article is devoted to the means of verbal influence, persuasion and suggestion in the series of books by Ernst Mouldashev entitled City of the Gods. The obje ctives ofthese means are to generate interest and credibility of reported information and developing a “divine” concept, to reduce the image of the author and to give the impression of authenticity. Cases are analyzed where the author successively copes with these tasks, as well as those where the lack of his language competence prevents him from fulfilling these goals.